Effect of Foot Massage Therapy on Fatigue Level of Chronic Kidney Failure Patients Undergoing Hemodialysis: A Rapid Review - Putri Karisa; Rezka Bahlail; Bambang Aditya Nugraha; Teni Sutianingsih (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2025)
Introduction: Fatigue is a common symptom in chronic renal failure patients undergoing hemodialysis. Fatigue has a negative impact on quality of life and general physical condition. There is a need for a treatment method that is easy, inexpensive, and can be done independently by families or caregivers to reduce the level of fatigue of chronic renal failure patients before, during and after hemodialysis. Aim: This study aims to determine the effect of foot massage on fatigue in CKD failure clients undergoing hemodialysis. Massage therapy is an alternative solution that can reduce fatigue levels. Methods: This study used a rapid review approach with the 2020 PRISMA guideline. Performed by searching articles from the PubMed, CINAHL, SAGE Journal, and Tandfonline databases and the Google Scholar search engine. The keywords used were chronic kidney disease, massage therapy, fatigue, and chronic kidney failure, massage therapy, and fatigue. Articles included in the study were full-text articles in English and Bahasa Indonesia, randomized control trial (RCT) and quasi-experimental study designs within the last five years (2018-2023), and focused on adult clients with chronic renal failure undergoing hemodialysis. Result: Seven articles analyzed found that massage therapy can reduce the fatigue level of chronic renal failure patients undergoing hemodialysis. The therapy time can be given with a duration of 15-60 minutes with a frequency of 2-3 times a week for 3-9 weeks. Conclusion: This intervention can be a recommendation for nurses to teach families about foot massage therapy. Further research is needed on the long-term benefits and family or caregiver involvement in its implementation and comparing the benefits of foot massage therapy with other complementary therapies to overcome fatigue in patients with chronic renal failure.